Innovations for Scaling Green Sectors - World Bank Group (Washington, DC: World Bank, 2019)
InfoDev - innovation and entrepreneurship report green sectors, such as renewable energy and sustainable agriculture, are some of the most important economic sectors for meeting the targets agreed in the Paris climate accord, achieving the sustainable development goals (SDGs), and realizing overall development gains in the coming decades. This study was initiated to shed light on the common challenges that have limited the scaling of green enterprises and the emergence of competitive green sectors in developing countries. It also aims to uncover and catalog emerging opportunities. Finally, the study offers key recommendations for donors, governments, development finance institutions (DFIs), and entrepreneurial supports organizations.